2018
DOI: 10.1021/acschembio.8b00555
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Epidermal Growth Factor Receptor Dimerization and Signaling Through Targeted Delivery of a Juxtamembrane Domain Peptide Mimic

Abstract: Overexpression and deregulation of the epidermal growth factor receptor (EGFR) are implicated in multiple human cancers and therefore are a focus for the development of therapeutics. Current strategies aimed at inhibiting EGFR activity include monoclonal antibodies and tyrosine kinase inhibitors. However, activating mutations severely limit the efficacy of these therapeutics. There is thus a growing need for novel methods to inhibit EGFR. One promising approach involves blocking the association of the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…It would be interesting to determine whether this shorter peptide influences the membrane spanning capacity of pHLIP or whether EJP18 could also be active in this way attached to pHLIP to give higher selectivity. While there were no links between EGFR expression and EJP18 induced toxicity, the peptide may be having some effects on receptor dimerisation and/or activation, similar to those seen with TE64562, T654, and pHLIP-JMA [17,41,42]. To interact with the EGFR JM domain, as initially predicted, would require crossing the plasma membrane to reach the target.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It would be interesting to determine whether this shorter peptide influences the membrane spanning capacity of pHLIP or whether EJP18 could also be active in this way attached to pHLIP to give higher selectivity. While there were no links between EGFR expression and EJP18 induced toxicity, the peptide may be having some effects on receptor dimerisation and/or activation, similar to those seen with TE64562, T654, and pHLIP-JMA [17,41,42]. To interact with the EGFR JM domain, as initially predicted, would require crossing the plasma membrane to reach the target.…”
Section: Discussionmentioning
confidence: 83%
“…However, uptake was monitored after 16 h and it is very difficult to determine its subcellular localisation. More recently a peptide consisting of a pH-dependent membrane spanning sequence ( pHLIP) in frame with a very short EGFR JM sequence 654-TLRRLLQ-660 was shown to inhibit EGRF dimerisation, inhibit cell migration and induce cytotoxicity and downstream effects [42]. It would be interesting to determine whether this shorter peptide influences the membrane spanning capacity of pHLIP or whether EJP18 could also be active in this way attached to pHLIP to give higher selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all HLA-G isoforms are capable of forming dimers, thereby enhancing its inhibitory capacity. Various studies have shown that preventing dimerization can inhibit the function of proteins [ 109 , 110 , 111 ]. For example, Qi et al demonstrated that inhibiting dimerization of the oncoprotein survivin leads to degradation of the protein and apoptosis in cancer cells [ 111 ].…”
Section: Hla-g As Target For Immune Checkpoint Inhibition In Cancementioning
confidence: 99%
“…However, most next generation drugs are also based on ATP-analogs and thus remain highly susceptible to developing inevitable resistance (56). Considering that dimerization of EGFR is a critical biological step required for its enzymatic activation, an ideal approach may be to take advantage of these features in developing novel EGFR-targeted drugs (57). Regarding this point, Mig6 segment 1-based peptides specifically targeting dimers can be considered as a novel potential drug particularly for dimerization-dependent mutant EGFR.…”
Section: Perspectivementioning
confidence: 99%